Minor and trace elements in skeletons of Arctic echinoderms. (September 2020) - Iglikowska, A.; Humphreys-Williams, E.; Przytarska, J.; Chełchowski, M.; Kukliński, P.
Abstract: We report the ratios of minor (K/Ca, Na/Ca, P/Ca, S/Ca) and trace elements (Al/Ca, Ba/Ca, Fe/Ca, Mn/Ca and Zn/Ca) in skeletons of five Arctic echinoderm species representing three classes: Asteroidea, Ophiuroidea, Crinoidea. We found that skeletons of Arctic echinoderms show a unique, species-specific trace element composition that may suggest that incorporation of elements into the skeleton is biologically controlled by the organism. On the other hand, the concentration of some minor elements in skeletal parts exhibit patterns that are consistent with elemental concentrations in seawater, indicating that formation of echinoderm skeletons is environmentally controlled. Seawater is the main source of ions and compounds needed for skeletal formation and maintaining similar concentrations most likely reduces the biological cost related to selective uptake of ions. Additionally, Al, Ba, Fe, Mg and Mn showed station specific variation in elemental concentration which again suggests that accumulation of metals can be shaped by environmental concentrations. Highlights: Skeletons of Arctic echinoderms show species-specific trace element composition. Incorporation of elements into echinoderm skeleton can be controlled biologically. Skeletal formation takes place in chemical equilibrium in ambient seawater. Skeletal accumulation of metals can be shaped by their seawater concentrations. Food may be a potential source of certain elements accumulated in skeletal tissue.